Mejora en la productividad de lechuga por aplicación de compost de cama de pollo - Okada, Elena; Carciochi, Walter; Pérez, Débora Jesabel; Cafaro La Menza, Nicolás; Adlercreutz, Enrique Gustavo; Hernandez Guijarro, Keren; Young, Brian Jonathan; Rizzo, Pedro Federico (Asociación Argentina de la Ciencia del Suelo, 2023)
Poster